Perilaku Antisosial Dalam Pandangan Islam - Haryani Putriana; Ihsan Mz (Jurnal Studia Insania, 2020)
This research was conducted to describe antisocial behavior in an Islamic perspective. Using qualitative methods in library research. Compile from various sources of relevant literature to find theories, propositions, principles, ideas, and opinions. Literary data is collected using the documentation method, so researchers get information not from several people as speakers, but from various written sources. This study reviews antisocial behavior from written documents in the form of published research and relevant books. While the study of Islamic view of this behavior is discussed through several propositions from the Koran and the Hadith. This research shows that antisocial behavior is not in line with the teachings of Islam because Islam through the Koran and Hadith asks each adherent to ta'aruf (know each other), interact with each other by promoting the ability of socialization, attitudes and good communication, while antisocial behavior is contrary to the principle.